World book 2001. Vol. 11 J-K / Mary Alice Anderson - Anderson, Mary Alice (2001)
Additional resources, early, important dates in Jackson's life, the world of president Jackson, Jackson´s fiest administration 1829-1833, vice presidents and cabinet, later years, additional resources, facts in brief, important January events, japan, government, people, where the people of japan live, way of life, the arts, the land, climate, average monthly weather, economy, production and workers by economic activities, economy of japan.